IMPLEMENTASI KEBIJAKAN ANGGARAN PENDAPATAN DAN BELANJA DESA DI DESA TOBELOS KECAMATAN IBU SELATAN KABUPATEN HALMAHERA BARAT - MALEMPI, LIANASTASIA; OGOTAN, MARTHA; DENGO, SALMIN (Sam Ratulangi University, 2019)
The purpose of this study was to determine the implementation of the APB-Desa policy in Tobelos Village, South Mother District, West Halmahera Regency. This study uses a descriptive-qualitative approach. The implementation of the APB-Desa policy is seen from the four dimensions of implementation of public policy, namely communication, resources, disposition, and bureaucratic structure. The research informants were village heads and village officials, BPD, LPMD, female elements, elements of community groups, and community leaders, all of whom were 8 informants. Data collection uses interview guidelines, while the analysis technique used is the analysis of interactive models from Miles and Hubernann. The results of the study show: (1) The implementation of the APB-Desa policy seen from the dimensions of communication is not optimal. Communication between the village government, BPD, LPM in the establishment and implementation of the APB-Desa is still weak. APB-Desa socialization to the community is still lacking. (2) The implementation of the APB-Desa policy seen from the dimension of human resources is still less supportive. The human resources of some village officials are quite good, but have not been optimally utilized for the implementation of the APB-Village properly. (3) The implementation of the APB-Desa policy seen from the disposition dimension is still weak. Commitment and consistency in implementing the APB-Desa properly and correctly is still lacking. The level of democracy in the establishment and implementation of the APB-Desa is also lacking. (4) The implementation of the APB-Desa policy seen from the dimensions of the bureaucratic structure is still not optimal. The mechanism and procedures for implementing the APB-Desa are clear, as well as the division of labor, but implementation is still often not appropriate. Keywords: Policy Impetetation, APB-Village.